Contribution of gender, marital status, and age to English language teachers' burnout - Mousavy, Seyedehhava; Hossein, Vahid Nimehchisalem (Australian International Academic Centre, 2014)
Teaching is a stressful job and can lead to teachers’ burnout. Teachers feel burned out when they experience high levels of emotional exhaustion and depersonalization but low levels of personal accomplishment (Maslach, 1999). A wealth of research is available on this subject but the findings are inconsistent. The present study surveyed the level of burnout among a randomly selected group of English language teachers (n = 315) in Malaysia. It also investigated whether these teachers’ gender, age and marital status could significantly contribute to their burnout levels. Maslach’s Burnout Inventory (Maslach & Jackson, 1986) was used to collect the data. According to the results, the teachers suffered from significantly high levels of burnout in reference to their PA scores. In comparison with the male teachers, female teachers reported significantly higher levels of burnout considering their emotional exhaustion (p = .008), depersonalization (p = .002) and personal accomplishment (p = .000). Additionally, older teachers (aged ≤ 40) were significantly more burned out than their younger colleagues (aged ≥ 30), regarding their depersonalization (p = .001) and personal achievement (p = .000) mean scores. Finally, married teachers indicated significantly higher levels of burnout compared with those who were not married. The study is expected to have useful implications for teachers, administrators, and researchers.